THE PRINCIPLE OF THE BEST INTEREST OF THE CHILD IN GRANTING CHILD CUSTODY RELATED TO DIVORCE - Bagenda, Christina; Carbonilla, Cicilia Hellena (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The principle of the best interest of the child is a fundamental principle universally recognized in the protection of children's rights. This principle is especially relevant in the context of divorce, where decisions regarding child custody must be made with a comprehensive consideration of the child's best interests. The purpose of this research is to analyze the application of the best interest of the child principle and to identify the main factors considered in making custody decisions in divorce cases in Indonesia. This research employs a normative legal research method with legislative and conceptual approaches. The sources of legal materials in this study include primary, secondary, and tertiary legal materials, and the data analysis technique used is qualitative analysis. The research findings reveal that the principle of the best interest of the child is applied in making child custody decisions in divorce cases in Indonesia by considering various factors related to the child's overall welfare, such as the child's age, the emotional bond between the child and the parents, the living environment, the child's safety and well-being, and the parents' ability to provide proper care. Other main factors considered include the parents' physical and mental health conditions, history of domestic violence, and the child's wishes or opinions if they are mature enough. The court will assess and consider all these factors comprehensively to decide on child custody based on what is most aligned with the best interest of the child in the divorce case.